Evaluasi Teknis Web Pemerintah Daerah Menggunakan Model Evaluasi Sintetik - Novi Prisma Yunita; Juarisman . (CV. ITTC INDONESIA, 2026)
Local government web platforms play an essential role in supporting the implementation of e-government through the provision of information, public services, and transparency. However, the technical quality of local government web platforms still exhibits significant variation, which may affect the effectiveness of digital services and public trust. This study aims to evaluate the technical quality of local government web platforms in South Kalimantan Province using a synthetic evaluation model with a focus on technical dimensions. The evaluation was conducted on official local government web platforms by integrating four main metrics: errors, accessibility, compatibility, and compliance with W3C standards. Data were collected through a combination of manual inspection and automated tools, then analyzed to identify patterns of technical issues and interrelationships among the evaluated metrics. The results indicate that the technical quality of local government web platforms is uneven. Various technical issues were identified, including weak management of link structures, limited implementation of accessibility principles, constraints in mobile device compatibility, and inconsistencies in the application of web development standards. These findings suggest that technical issues do not occur in isolation but are interrelated and require an integrated improvement approach. This study emphasizes the importance of systematic and continuous technical evaluation as a foundation for the development of local government web platforms. The synthetic evaluation model applied in this study can be replicated to assess the technical quality of local government web platforms in other contexts and serve as a basis for formulating technical recommendations to support more inclusive, reliable, and user-oriented digital public services.